Law No. 25/1986 Promulgating the Evidentiary Law As to the Civil & Commercial Articles = قانون الإثبات في المواد المدنية والتجارية. (2025)
1. General Provisions -- 2. Written evidences -- 3. The testimonial of witnesses -- 4. Presumptions and the proof of the rule absolute -- 5. Admission and the questioning of litigants -- 6. the oath -- 7. Right of visitation -- 8. the Expertise.